PENGELOLAAN EVENT GEDUNG SATE FESTIVAL 2018 OLEH DINAS PARIWISATA DAN KEBUDAYAAN JAWA BARAT - Ariandani, Raysha Nanda; Novianti, Evi; Setianti, Yanti (Jurnal Common, 2020)
The realization of West Java, the inner and inner champion with innovation and collaboration. â€The West Java Disparbud seeks to preserve local cultural assets and make art and culture effective as regional assets that support the development of tourism in West Java in the frame of local wisdom.â€¦ SS One of the implementation of regional tourism promotion events held by the West Java Disparbud Marketing Sector is the Gedung Sate Festival 2018 event. Model Planning, Research, and Evaluation offers a broad research and planning methodology. With a descriptive approach. Evaluation is also carried out through media monitoring. Furthermore, the West Java Tourism and Culture Office conducted an evaluation by looking at reports on food product tenants sales of tenants, through media coverage and seeing how many media covered the 2018 Gedung Sate Festival event, through interviews with visitors at media, community feedback through social media. And based on the information we got, the response was positive and it can be said that the 2018 Gedung Sate Festival was successfully held .. The researcher recommends that planning should be thorough and anticipating obstacles that occur both in terms of publication, coordination, evaluation, research processes and technical implementation. In addition, we can be more sensitive to the obstacles of the 2018 Gedung Sate Festival.